CyAbrB2 Contributes to the Transcriptional Regulation of Low CO2 Acclimation in Synechocystis sp. PCC 6803. (16th September 2016) - Orf, Isabel; Schwarz, Doreen; Kaplan, Aaron; Kopka, Joachim; Hess, Wolfgang R.; Hagemann, Martin; Klähn, Stephan
Abstract: Acclimation to low CO2 conditions in cyanobacteria involves the co-ordinated regulation of genes mainly encoding components of the carbon-concentrating mechanism (CCM). Making use of several independent microarray data sets, a core set of CO2 -regulated genes was defined for the model strain Synechocystis sp. PCC 6803. On the transcriptional level, the CCM is mainly regulated by the well-characterized transcriptional regulators NdhR (= CcmR) and CmpR. However, the role of an additional regulatory protein, namely cyAbrB2 belonging to the widely distributed AbrB regulator family that was originally characterized in the genus Bacillus, is less defined. Here we present results of transcriptomic and metabolic profiling of the wild type and a Δ cyabrB2 mutant of Synechocystis sp. PCC 6803 after shifts from high CO2 (5% in air, HC) to low CO2 (0.04%, LC). Evaluation of the transcriptomic data revealed that cyAbrB2 is involved in the regulation of several CCM-related genes such as sbtA/B, ndhF3/ndhD3/cupA and cmpABCD under LC conditions, but apparently acts supplementary to NdhR and CmpR. Under HC conditions, cyAbrB2 deletion affects the transcript abundance of PSII subunits, light-harvesting components and Calvin–Benson–Bassham cycle enzymes. These changes are also reflected by down-regulation of primary metabolite pools. The data suggest a role for cyAbrB2 in adjusting primary carbon and nitrogen metabolism to photosynthetic activity under fluctuating environmental conditions. The findings were integrated into the current knowledge about the acquisition of inorganic carbon (Ci), the CCM and parts of its regulation on the transcriptional level.